PEMBERDAYAAN SMART PARENTS SMART KIDS BELAJAR POLA ASUH DAN STATUS GIZI BERSAMA DALAM TUMBUH KEMBANG ANAK - Purnamasari, Ira; Prayitno, Teguh; Astofani, Zaki; Prihatiningsih, Farida (Program Kreativitas Mahasiswa - Pengabdian Kepada Masyarakat, 2013)
One important element of health is a matter of nutrition, malnutrition among children under five can cause negative effects such as brain shrink, prone to disease, weight and height are not in accordance with the age and can lead to death of the child. Children suffering from PEM especially at the level of malnutrition severe constraints in physical growth and mental development, resistance to disease decreases thereby increasing morbidity and risk of death is high. Relative risk of mortality for patient with severe PEM 8,4 times, medium PEM 4,6 times and light PEM 2,4 times lighter than good nutrition. Methods in the delivery of information in the form of counseling with the help of instruments in the form of leaflets, booklets, CD audiovisual and cooking demonstration MP-ASI, so that we convey the information accurately and easily accepted in the general public. Related malnutrition and PEM (protein energy malnutrition) in the Bulak Banteng, Kenjeran, Surabaya. Can be overcome by providing health education related parenting, providing adequate nutrition and is a very effective way. The level of knowledge of mothers in the community, especially with children PEM is was very instrumental in the growth and development of children with socialization health help reduce the incidence of malnutrition in East Java.